(untitled) (Journal of Applied Learning and Teaching, 2024)
Higher Education institutions, at least in nominal ‘Western’ contexts, oversell a dressed-up version of ‘excellence’ to draw in students, but they have more firmly in their sight a vision of the commercial bottom line. This research study, firmly grounded in the author’s experience of postgraduate education, posits that the marketised, neoliberal conception of ‘excellence’ both covers a hidden truth that these institutions are content just to get learners ‘over the line’ and hides a more authentic, bottom-up conception of ‘excellence’ which appears when the voices of learners and educators are heard above the managerialist chatter and when teaching well is considered. The paper presents its review of the field as a critically evocative autoethnography, with the author positioned as a witness to the lexical slaughter of ‘excellence’, amongst other terms suborned by the neoliberalist academy. Within its chorus of voices, it introduces the reflective critical incidents of three postgraduate supervisors or mentors telling of their realisations that their institutions are more interested in getting students ‘over the line’ in a timely fashion than in facilitating opportunities for authentic excellence. Methodologically, then, the study presents three narratives as evidence in a narrative enquiry embedded in the broader autoethnography, as is often the case in professional practice research. The paper is positioned on the cusp of COVID-19’s aftermath and suggests that higher education organisations are on track to miss the opportunities to begin dismantling neoliberal thought that the pandemic afforded. Instead, they condemn themselves to ‘mediocracy’ – rule by the mediocre churning out mediocrity under the guise of a shopfront of gaudy but vacuous ‘excellence’.